Mapping the Development of E-Learning-Based Learning During and Post-COVID-19 Pandemic (2020-2024) with Bibliometric Analysis - Sasongko, Farah Adibah; Andhim, Muk; Maksum, Muh. Nur Rochim; Shobahiya, Mahasri; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to map the development and direction of educational research in Scopus-indexed publications. This study uses bibliometric analysis techniques to explore all journals indexed in the Scopus database on E-learning from 2020 to 2024, namely during the pandemic - post-Covid-19 pandemic. The data was analyzed using Excel and R / R-Studio. VOSviewer is used to visually analyze the emergence of keywords and document citations simultaneously. The author found 4510 publications that match the functions, subjects, and criteria set. The results of this study show the most publications on E-learning in 2023. The United States is the country that contributes the most publications, with an affiliation from the University of Florida. Hwang G. J is the most productive author on the E-learning theme. The bibliometric analysis conducted is limited to Scopus data. Other national and international databases are not taken into account in this study. This study presents a brief overview of the literature that researchers can access in the field of education and provides recommendations for future research.